The effect of EMG triggered electrical stimulation plus task practice on arm function in chronic stroke patients with moderate-severe arm deficits - Singer, B.; Vallence, A.; Cleary, S.; Cooper, Ian; Loftus, A. (I O S Press, 2013)
Purpose: We examined the feasibility and outcome of electromyographically triggered electrical muscle stimulation (EMG-ES) plus unilateral or bilateral task specific practice on arm function in chronic stroke survivors with moderate-severe hemiplegia. Transcranial magnetic stimulation was used to examine inter-hemispheric inhibition (IHI) acting on the stroke-affected hemisphere in a subset of eight participants.Methods: Twenty-one stroke survivors (14 males; mean time post stroke 57.9 months) participated in this pilot investigation. Participants underwent a six-week program of daily EMG-ES training with random assignment to concurrent task practice using the stroke-affected hand only or both hands. The upper-extremity subscale of the Fugl-Meyer (FMUE) and the Arm Motor Ability Test (AMAT) were completed at baseline, 0-, 1-, and 3-months post-intervention.Results: Following the intervention, FMUE (F(3,57) = 3.89, p = .01, ηp2 = .17) and AMAT (F(3,57) = 12.6, p = .01, ηp2 = .39) scores improved, and remained better than baseline at three months re-assessment. The difference between groups was not significant. A non-significant decrease in IHI was observed post-intervention.Conclusions: An intensive program of EMG-ES assisted functional training is feasible, well tolerated, and leads to improvements in moderate-severe deficits of arm function post stroke. Larger placebo controlled studies are needed to explore any advantage of bilateral over unilateral EMG-ES assisted training.